2004
DOI: 10.1158/1078-0432.ccr-04-0220
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Clinical Characterization of the Basal-Like Subtype of Invasive Breast Carcinoma

Abstract: Purpose: Expression profiling studies classified breast carcinomas into estrogen receptor (ER)؉/luminal, normal breast-like, HER2 overexpressing, and basal-like groups, with the latter two associated with poor outcomes. Currently, there exist clinical assays that identify ER؉/luminal and HER2-overexpressing tumors, and we sought to develop a clinical assay for breast basal-like tumors.Experimental Design: To identify an immunohistochemical profile for breast basal-like tumors, we collected a series of known ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

137
2,200
16
105

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 2,290 publications
(2,491 citation statements)
references
References 26 publications
137
2,200
16
105
Order By: Relevance
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Our study confirms and extends the previously reported findings of the basal-like carcinoma immunophenotype. [5][6][7][8]10 In addition, we demonstrate the presence of in situ carcinoma as the likely precursor lesion for invasive basal-like carcinoma.…”
Section: Discussionmentioning
confidence: 58%
“…5 The characteristic immunohistologic phenotype of these tumors is the 'triple negative' receptors of estrogen, progesterone and HER-2/neu, while expressing keratins CK5/6, CK14, CK17, vimentin and HER-1. [5][6][7][8][9][10][11] While the invasive basal-like neoplasms are reasonably well characterized morphologically and immunohistochemically, there is little data about the precursor lesion(s) for the entity.…”
mentioning
confidence: 99%
“…(II) Basal-like breast carcinomas As NGFR positivity was restricted to ER negative (11/11 cases) and 10 of these cases showed expression of basal-like immunohistochemical markers, the prognostic impact of NGFR was assessed in a second cohort of 37 high-grade ductal carcinomas classified as basal-like according to Nielsen et al 26 immunohistochemical panel. In this cohort, NGFR expression was observed in 38% of the cases (Figure 5e-h) and was associated with lack of lymph node metastasis at diagnosis (Po0.001).…”
Section: Tumours With Myoepithelial Differentiationmentioning
confidence: 99%
“…There are several lines of evidence to suggest that highgrade breast carcinomas expressing basal/myoepithelial markers have distinct pathological features, expression profiles and, most importantly, clinical behaviour when compared to high-grade breast carcinomas devoid of basal-like differentiation. [23][24][25][26][27][28][29][30] The landmark studies of Perou et al 23 and Sorlie et al 24,25 revealed basal-like breast carcinomas to be more aggressive than oestrogen receptor (ER)-positive cancers, the former having significantly shorter disease-free and overall survival. Furthermore, recent data from our laboratory have suggested that basal tumours are heterogenous in terms of their molecular genetic profiles and that there might be a subgroup with a more favourable prognosis.…”
mentioning
confidence: 99%
See 1 more Smart Citation